Analysis of clinical management of infected breast implants and of factors associated to successful breast pocket salvage in infections occurring after breast reconstruction. (June 2018) - Franchelli, Simonetta; Pesce, Marianna; Baldelli, Ilaria; Marchese, Anna; Santi, Pierluigi; De Maria, Andrea
Highlights: Retrospective Review on sequential implant breast reconstructions, with definition of infection (possible, probable, and proven). Analysis of factors influencing entry into clinical attempts at infected implant salvage. Outcome (salvage vs. failure) evaluation on proven infections. A relevant clinical difference emerged depending on salvage management, with high success rates in proven infections. Implant salvage varied from 60 to 100% depending to the clinical management Abstract: Objectives: Considerable efforts have been devoted so far to improve salvage procedures of infected breast implants in absence of defined guidelines or validated clinical protocols. Within a cohort of prospectively recruited patients who underwent breast reconstruction, we performed a retrospective review of proven implant infections in order to describe factors contributing to management success. Methods: We collected data in 1293 consecutive patients who underwent two stage (expander + prosthesis) breast reconstruction with at least 12 months of follow-up. Demographic data, timing of infection, type of microorganism, intent of salvage, fate of the implant, type of antibiotic treatment and follow-up were recorded in a prospective data collection on clinical records. Results: Implant infections occurred in 103 of 1293 patients (8%). Among these, 73 (71%) were proven infections with confirmed microbiology. Implant pocket salvage was attempted in 43/73 (59%). patients A higher proportion of expander implant pockets were successfully saved compared to prosthetic pocket (p = 0, 04). Gram-positive microrganisms represented the majority of etiologic agents, with coagulase negative staphylococci prevailing over Staphylococcus aureus . No association was observed between success rate and type of infecting microorganism. A higher proportion of patients with previous or intraoperative radiotherapy or with perioperative chemotherapy underwent an attempt of implant salvage (p = 0, 081 and 0, 0571 trend, respectively). No single antibiotic regimen was superior to the others in terms of success rate. Implant pocket salvage was higher in expanders compared to prostheses (74% vs 33% p = 0, 04). Higher success rates in implant pocket salvage were evident when implant replacement was preceded and followed by antibiotic treatment compared to inpatient antibiotic treatment alone (100% versus 57%, p = 0, 035). Conclusion: Patient selection in clinical practice leads to differences in patients with breast implant infection who are considered for attempts at implant salvage vs. those who are treated with implant removal. Salvage of breast implant pockets can be obtained in the majority of patients with combined one-step implant replacement surgery and antibiotic treatment. Increased efforts and protocols to recruit patients into pocket salvage management are needed.